Optimal selection of precision points for function synthesis of spherical 4R linkage - Suixian, Y; Hong, Y; Tian, G Y (Proceedings of the Institution of Mechanical Engineers. Part C, Journal of mechanical engineering science, 2009)
Abstract In order to reduce synthesis error, a new approach is reported to select precision points for function synthesis of spherical 4R linkages. Based on a closed-form symbolic solution of the set of function synthesis equations of spherical 4R linkages, the structure error equation has been derived by introducing a scaling factor. After this, an optimization model was constructed to search for the precision points. The initial solution of the optimization model was chosen using a numerical interpolation method. The global optimal solution was obtained using the fractal algorithm. To illustrate this, an example is presented and discussed before finally deriving conclusions.